The Effect of Amount and Tangibility of Endowment and Certainty of Recipients on Selfishness in a Modified Dictator Game. Issue 3 (June 2014) - Chang, Shao-Chuan; Lin, Li-Yun; Horng, Ruey-Yun; Wang, Yau-De
Taiwanese college students ( N =101) participated in the study to examine the effects of the amount of an endowment, the tangibility of an endowment, and the certainty of the recipient on selfishness in a modified dictator game. Results showed that dictators were more selfish when allocating tangible (money) than less tangible (honor credits) endowments. Selfishness was higher when large amounts of money were involved. The certainty of the recipient was manipulated by whether the recipient was chosen and announced before or after the decision. Unexpectedly, participants were more self-interested in the certain-recipient condition than in the uncertain-recipient condition. In the honor condition, the amount of an endowment and the certainty of the recipient did not affect participants' allocations.